Media Monitoring Model in Public Relations of BUMN (State-owned enterprises) Companies - Oktaria Sukmayani; Jamroji Jamroji (LPPM Institut Pesantren KH. Abdul Chalim, 2021)
Media monitoring is a form of Public Relations activity used in many companies, including the companies in Indonesia, to monitor mass media coverage and to find out current issues among the public. One of the companies that implement media monitoring activities in PT Perkebunan Nusantara (PTPN) X. PTPN X is a state-owned company engaged in the sugar and tobacco business in Indonesia. The purpose of this study is to describe the monitoring media model in the Public Relations of BUMN companies, namely PT Perkebunan Nusantara X Surabaya. In this study, the researcher used a qualitative descriptive approach through data collection by observation, interviews, and documentation. The theory used was the theory of Evaluation of Public Relations. One form of Evaluation of Public Relations is media monitoring. The results of this study found that the media monitoring model applied by PTPN X was a media monitoring model in normal conditions and the model during a crisis. This research is indispensable in the development of media monitoring practices and studies in Indonesia, especially for the Public Relations/Public Relations department.